2011
DOI: 10.1002/ps.2132
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of F1, F2 and F3 hybrids between weedy rice and transgenic glufosinate‐resistant rice

Abstract: There was no significant decrease in the composite agronomic performance of any of the hybrids compared with weedy rice. This implies that gene flow from transgenic cultivated rice to weedy rice could occur under natural conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 61 publications
1
12
0
3
Order By: Relevance
“…It has been demonstrated that after hybridisation, the transgene can be stably transmitted across the different generations of F2 and F3 (Song et al . ), as also observed here. Further, the segregation for herbicide resistance fitted a 3:1 genetic ratio in F2, confirming that resistance was controlled in the hybrid and further generations by the dominant nuclear transgene.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that after hybridisation, the transgene can be stably transmitted across the different generations of F2 and F3 (Song et al . ), as also observed here. Further, the segregation for herbicide resistance fitted a 3:1 genetic ratio in F2, confirming that resistance was controlled in the hybrid and further generations by the dominant nuclear transgene.…”
Section: Discussionsupporting
confidence: 91%
“…Crop-to-weed gene flow is of special concern when transgenes are involved as it leads to the movement of genetically modified (GM) genes to weeds that might confer survival advantages that enable them to outcompete local strains (Oard et al 2000;Lu and Snow 2005;Cao et al 2006;Zhang et al 2006;Yang et al 2012). Crop-weed hybrids have been found to show variable levels of adaptability and survival capabilities (Burgos et al 2008(Burgos et al , 2014Reagon et al 2011;Song et al 2011;Yang et al 2012). Morphological (Sato 2000).…”
Section: Outcrossing and Its Associated Concerns In Weedy Ricementioning
confidence: 99%
“…As already mentioned, the gene flow between resistant rice varieties and weedy rice has generated hybrid weedy rice populations with variable traits. Herbicide-resistant weedy rice grown in rice fields were found to have short heights, early flowering, and reduced seed shattering (Burgos et al 2008, 2014Reagon et al 2011;Song et al 2011;Yang et al 2012). Furthermore, the insect-resistant weedy rice hybrids generated from crossing weedy rice with insectresistant cultivated varieties have also led to increased seed production .…”
Section: Potential Value Of Weedy Ricementioning
confidence: 99%
“…Glufosinateresistant rice was deregulated (approved for sale) but never commercialized, perhaps partly because of the potential problem of gene flow to weedy rice and nontransgenic rice (Oard et al, 2000;Olofsdotter et al, 2000;Sanchez-Olguin et al, 2009;Song et al, 2011). The adoption of glufosinateresistant crops has been only a small fraction of the HR crop market, primarily because glyphosate is a more effective herbicide than glufosinate on many weed species.…”
Section: Herbicidementioning
confidence: 97%